2019
DOI: 10.1016/j.bpj.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Prenylation Is Required for Bivalent Binding with Calmodulin in a Nucleotide-Independent Manner

Abstract: Deregulation of KRAS4b signaling pathway has been implicated in 30% of all cancers. Membrane localization of KRAS4b is an essential step for the initiation of the downstream signaling cascades that guide various cellular mechanisms. KRAS4b plasma membrane (PM) binding is mediated by the insertion of a prenylated moiety that is attached to the terminal carboxy-methylated cysteine, in addition to electrostatic interactions of its positively charged hypervariable region with anionic lipids. Calmodulin (CaM) has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 48 publications
7
63
0
Order By: Relevance
“…Remarkably, farnesyl cysteine methyl ester (FCME), representing the farnesylated C-terminal residue of KRAS4b, and farnesol alone, an alcohol derivative of the farnesyl moiety, induced a similar pattern of extensive Ca 2+ -dependent chemical shift perturbations in 15 N CaM without causing line broadening [55]. Consistently, addition of a farnesylated polybasic 6-mer peptide from the KRAS4b C-terminus produced nearly identical changes in the CaM spectrum [54].…”
Section: Structural Characterization Of Cam Binding To Kras4bmentioning
confidence: 87%
See 3 more Smart Citations
“…Remarkably, farnesyl cysteine methyl ester (FCME), representing the farnesylated C-terminal residue of KRAS4b, and farnesol alone, an alcohol derivative of the farnesyl moiety, induced a similar pattern of extensive Ca 2+ -dependent chemical shift perturbations in 15 N CaM without causing line broadening [55]. Consistently, addition of a farnesylated polybasic 6-mer peptide from the KRAS4b C-terminus produced nearly identical changes in the CaM spectrum [54].…”
Section: Structural Characterization Of Cam Binding To Kras4bmentioning
confidence: 87%
“…Structural data show that the KRAS4b-CaM interaction is principally mediated through sequestration of the KRAS4b farnesyl group, likely further stabilized by electrostatic contacts between the polybasic KRAS4b HVR and the acidic CaM surface [55]. Ca 2+ -CaM therefore sequesters the hydrophobic KRAS4b membrane localization moiety, and KRAS4b association with Ca 2+ -CaM was reported to be~10-fold tighter than with the membrane [54,56]. Consistently, surface plasmon resonance (SPR) experiments with a lipid bilayer membrane captured on the biosensor chip showed that Ca 2+ -CaM extracted KRAS4b from this bilayer in a nucleotide-independent manner [46], and the transfer of prenylated KRAS4b between vesicles was accelerated by Ca 2+ -CaM [57].…”
Section: Structural Characterization Of Cam Binding To Kras4bmentioning
confidence: 99%
See 2 more Smart Citations
“…Protein production E. coli proteins were expressed as described in (21). For insect cell expression, baculoviruses were generated by transfection of bacmid DNA into Sf9 cells as previously described (22). Titered viruses were used at an MOI of 3 to infect Tni-FNL cells (23) which were grown at 21 °C for 72 hours prior to harvest.…”
Section: Plasmids For Mammalian Expression Were Made By Subcloning Enmentioning
confidence: 99%